The clinical outcomes and quality of life in patients with Guillain- Barré syndrome: a literature review - Rosa De Lima Renita Sanyasi (Published by Universitas Gadjah Mada, 2025)
Guillain-Barre syndrome (GBS) is an immune-mediated condition that targets the roots of the spinal cord and peripheral nerves. While most patients with GBS can achieve complete recovery with appropriate management, some may experience long-term sequelae that adversely impact their quality of life (QoL). Clinical outcomes are measured variables in research to evaluate the effects of interventions or exposures on a particular population’s health. Patients with GBS may experience suboptimal clinical outcomes due to post-GBS disabilities, which may result from complications or residual symptoms of the syndrome. These disabilities can impede daily functioning and significantly lower QoL, often requiring patients to alter their lifestyles, work, and social interactions. Quality of life is a subjective assessment of how individuals perceive their circumstances in relation to their goals, influenced by their cultural and value systems. Various tools are available to assess the quality of life for GBS patients. The clinical outcomes and QoL for post-GBS patients are diverse and shapedby various factors. Through the early identification of these factors, clinicians can enhance management strategies to improve both clinical outcomes and the overall QoL for individuals recovering from GBS.